Marketability of Banana Cheesecake (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Bananas are a healthy source of fiber, potassium, vitamin B6, and vitamin C, as well as various antioxidants and phytonutrients. Bananas are high in antioxidants, which protect from free radicals. We come into contact with free radicals every day, from the sunlight to the lotion you put on your skin. The researchers used an experimental research design. The respondents were chosen through simple random sampling, and a survey questionnaire was used to gather the data. The respondents assessed banana cheesecake in terms of several variables. In terms of presentation, the respondents obtained a weighted mean of 3.84, with the verbal interpretation of strongly acceptable. In terms of aroma, the respondents obtained a weighted mean of 3.83, with the verbal interpretation of strongly acceptable. In terms of taste, the respondents obtained a weighted mean of 3.87, with the verbal interpretation of strongly acceptable. In terms of price competitiveness, the respondents obtained the weighted means of 3.5, with the verbal interpretation of strongly acceptable. The respondents recommended improving the packaging and stating the nutritional value of the product in the packaging.
Keywords: banana, cheesecake